Detection of Intrusions and Malware, and Vulnerability Assessment 9th International Conference, DIMVA 2012, Heraklion, Crete, Greece, July 26-27, 2012, Revised Selected Papers - Flegel, Ulrich; Markatos, Evangelos; Robertson, William; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed post-proceedings of the 9th International Conference on Detection of Intrusions and Malware, and Vulnerability Assessment, DIMVA 2012, held in Heraklion, Crete, Greece, in July 2012. The 10 revised full papers presented together with 4 short papers were carefully reviewed and selected from 44 submissions. The papers are organized in topical sections on malware, mobile security, secure design, and intrusion detection systems (IDS).
Using File Relationships in Malware -- Understanding DMA Malware -- Large-Scale Analysis of Malware Downloaders -- Juxtapp: A Scalable System for Detecting Code Reuse among Android Applications -- ADAM: An Automatic and Extensible Platform to Stress Test Android Anti-virus Systems -- A Static, Packer-Agnostic Filter to Detect Similar Malware Samples -- Experiments with Malware Visualization -- Tracking Memory Writes for Malware Classification and Code Reuse Identification -- System-Level Support for Intrusion Recovery -- NetGator: Malware Detection Using Program Interactive Challenges -- SmartProxy: Secure Smartphone-Assisted Loginon Compromised Machines -- BISSAM: Automatic Vulnerability Identification of Office Documents -- Self-organized Collaboration of Distributed IDS Sensors -- Shedding Light on Log Correlation in Network Forensics Analysis.
Keywords: Computer science; Computer Communication Networks; Computer network architectures; Data protection; Computer Science; Systems and Data Security; e-Commerce/e-business.; Computer Communication Networks; Computer System Implementation